Wooden Furniture Trade in Ethiopia: Current Conditions and Future Prospects - Kassaye, Tensaye Abate; Abebe, Mister; Ferede, Alemtsehaye (PT FORMOSA CENDEKIA GLOBAL, 2025)
Demand for wooden furniture in Ethiopia is rapidly increasing due to population growth, urbanization, and economic development. This demand is met through both local production and imports, yet limited information exists on the sector’s trade dynamics. This study assessed the status and trends of Ethiopia’s wooden furniture import-export market using data from the Ethiopian Customs Commission (2009–2020). Descriptive statistics and the ARIMA model in STATA were applied. Results show average annual imports and exports of 12,650.9 and 429.8 tonnes, respectively. Ethiopia spent an average of US 22.6 million on imports while earning only US 1.7 million from exports, indicating a trade deficit. By 2040, import costs are projected to rise to US 29.2 million. However, with proper investment and policy focus, local wooden furniture production can boost national revenue and reduce import dependency. Thus, expanding domestic wooden furniture manufacturing is vital to meet future demand and support economic growth.